Cystic Fibrosis Virtual Patient Advocacy - Cottrell, Stacey (My University, 2021)
Cystic Fibrosis is a rare life-limiting genetic disorder that affects 30,000 people in the United States. The CF population has seen an increase in their life expectancy as new research, therapies and technology has improved their quality of life. Knowledge of these resources is important for empowering patients and caregivers to engage in and coordinate their own care and wellness. The Cystic Fibrosis Foundation’s Central Eastern Carolinas chapter is interested in connecting the population to the available resources. Virtual methods of connection become important in a community which requires social distancing due to disease process and increased risk of infection. Virtual communication is even more vital, as Coronavirus disease (COVID-19) limits interactions with others. A virtual patient advocate (VPA) and quick response (QR) code are the identified methods of providing awareness and education while helping establish a relationship with local resources through local CFF chapters.
Keywords: advocacy, virtual, resources, awareness, Cystic Fibrosis